Suntzu on Management: The Art of War in Contemporary Business Strategy - Foo Check Teck; Sun Tzu (Singapore Butterworth-Heinemann Asia, 1995)
Discusses the art of war in contemporary business strategy. Its findings are based on the results of a unique survey of strategic planning processes in the ASEAN region.
Age Group: Adult
Includes bibliographical references.
Keywords: Management; Nonfiction; Strategic Planning -- Asia, Southeastern; Sunzi, 6th Cent. B.C. Views On Management